Associations of subjective age trajectories with loneliness and stress across adulthood - Anna E. Kornadt; Markus Wettstein; Anthony Lepinteur; Claus Vögele; Conchita D’Ambrosio (PLoS ONE, 2025)
Subjective age, that is the age a person feels like in relation to their chronological age, is indicative of a variety of biological, psychological, and social aging processes. Despite its importance, studies that investigate multi-variate, dynamic, longitudinal relations of subjective age with its potential determinants and potential mechanisms of these relations have so far rarely been employed. In the current study, we focus on loneliness as a potential subjective age determinant. As loneliness affects a variety of psychosocial and health outcomes across life and is stereotypically perceived as a feature of old age, we investigate whether loneliness is related with levels and changes in subjective age. We furthermore test whether this association is mediated via self-reported stress. N =  5,594 participants aged 18 – 93 years (Mage =  50.41, SD =  15.99) who participated in a longitudinal survey comprising up to three measurement occasions over a time span of 2.5 years reported their loneliness, subjective age, and stress as well as sociodemographic and health-related covariates. We employed latent growth modeling and found that, when controlling for sociodemographic and health-related covariates, higher loneliness was related to an older subjective age cross-sectionally and to a steeper increase in subjective age over time. These relations were mediated via stress; however, the relation between stress and subjective age was no longer statistically significant when including the covariates. All associations were qualified by significant interactions with chronological age, albeit in different directions. Our findings attest to associations between loneliness, stress and subjective aging experiences and highlight the need for an age-informed approach when planning further studies and interventions.